2015
DOI: 10.1007/s11032-015-0384-4
|View full text |Cite
|
Sign up to set email alerts
|

Genetic analysis of kernel weight and kernel size in wheat (Triticum aestivum L.) using unconditional and conditional QTL mapping

Abstract: Thousand kernel weight (TKW) is commonly regarded as a complex trait in wheat. Both unconditional and conditional quantitative trait locus (QTL) analyses were conducted using software QTLNetwork 2.0 in four environments to evaluate the genetic relationships between TKW and kernel size. These analyses involved a set of 182 F 8:9 recombinant inbred lines derived from ''Shan-nong01-35 9 Gaocheng9411'' with a genetic linkage map consisting of 503 molecular markers. Additive effects, epistatic effects, and genotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
20
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(22 citation statements)
references
References 60 publications
2
20
0
Order By: Relevance
“…A number of QTL for TKW and kernel size on chromosome 5B have been reported in previous studies ( Groos et al, 2003 ; Breseghello and Sorrells, 2006 ). Among them, QTkw.ncl-5B.2 and QTw-5B.1 associated with Xgwm213 were located on the 5BL ( Ramya et al, 2010 ); QTkw5B.1-12 and QKw5B.1-12 were located on 5B ( Li et al, 2015 ). Sarma et al (2000) reported two possible loci affecting flowering time on the long arm of the 5B chromosome ( Vrn-B1 and Eps ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…A number of QTL for TKW and kernel size on chromosome 5B have been reported in previous studies ( Groos et al, 2003 ; Breseghello and Sorrells, 2006 ). Among them, QTkw.ncl-5B.2 and QTw-5B.1 associated with Xgwm213 were located on the 5BL ( Ramya et al, 2010 ); QTkw5B.1-12 and QKw5B.1-12 were located on 5B ( Li et al, 2015 ). Sarma et al (2000) reported two possible loci affecting flowering time on the long arm of the 5B chromosome ( Vrn-B1 and Eps ).…”
Section: Discussionmentioning
confidence: 99%
“…And most of them, such as TaCwi-A1 ( Ma et al, 2012 ), TaCKX6-D1 ( Zhang L. et al, 2012 ), TaGS1 ( Guo et al, 2013 ), TaGS5 ( Ma et al, 2016 ), and TaGW2 ( Su et al, 2011 ) were cloned through homologous cloning. Although multiple major and stable QTL controlling kernel shape and size were identified on chromosomes 2A ( Wu et al, 2015 ), 2D ( Breseghello and Sorrells, 2007 ; Ramya et al, 2010 ; Cui et al, 2016 ), 4A ( Cui et al, 2016 ), 5A ( Wu et al, 2015 ), 5B ( Breseghello and Sorrells, 2007 ; Ramya et al, 2010 ; Li et al, 2015 ) and 6A ( Zhang et al, 2013 ), they were defined in a relatively large chromosome interval due to the limited numbers of markers.…”
Section: Introductionmentioning
confidence: 99%
“…There is a negative association between GW and GM 2 (Slafer et al, 1996 , 2014 ; Saeidi and Abdoli, 2015 ) indicating compensation, although it has been shown that in the case of wheat the compensation is not competitive (Slafer et al, 1996 ) and a positive association between these two yield components has also been reported (Nouri-Ganbalani et al, 2009 ; Motzo et al, 2010 ). Several studies reported GW as the yield component with the highest heritability in bread wheat and Durum wheat (Nachit et al, 1995 ; Royo et al, 2002 ; García del Moral et al, 2003 ; Rharrabti et al, 2003 ; Wang et al, 2009 ; Li et al, 2015 ). In contrast, GM 2 has shown similar heritability to yield in bread wheat and Durum wheat (Nachit and Ketata, 1991 ; Acevedo, 1992 ) thus yield improvements under water stress using GM 2 have had limited success, since GM 2 is as unpredictable as yield itself (Dolferus et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…Many QTLs controlling grain number per ear, ear weight, and ear length had been reported on chromosomes 2A, 2B, 2D, 4A, 5A, 5D, and 6B [ 20 22 ], where most variations were only observed in Yangfumai 4. The QTLs controlling thousand kernel weight were identified on chromosomes 2A, 2D, 3B, 4B, 6A, 7A, and 7B [ 21 , 23 ], and those controlling lodging resistance were discovered on chromosomes 2A, 2D, 3B, 5A, 5B, and 5D [ 24 26 ], on which Ningmai 13 and Yangfumai 4 both presented same alleles. These chromosome regions may contain QTLs associated with thousand kernel weight and lodging resistance.…”
Section: Discussionmentioning
confidence: 99%